COMMUNITY EMPOWERMENT EFFORTS THROUGH COLLECTING COIN FUNDS IN NGRONGGOT VILLAGE, NGRONGGOT DISTRICT, NGANJUK REGENCY - Moh. Hasyim Afandi; Zainal Arifin; Muhammad Saikhon; Tri Wahyudi Ramdhan (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2021)
Nahdlatul Ulama, the majority of whose members are mostly from the lower class,initiated to collect coins from members. Regardless of the rich or poor all members areasked to participate. On this basis, the aim of the Coin Care Movement Program is themovement of the NU population to collect coins from the houses of Nahdliyin residentswhose benefits are to solve various problems in aspects of life and realize Jam'iyyahindependence. The results of the mentoring activities obtained were (1) the condition ofthe Ngronggot village community before the mentoring although the spirit of diversityand social solidarity was very high but still individual, (2) The form of the assistanceactivities carried out included awareness of their potential so that they always thinkpositively, and vocational training the following applications so that new entrepreneursemerge (3) After the mentoring program is complete, community trust in self-potential,both economic and religious, emerges together to support each other both in religious andsocial activities.